Age-related taxation of bequests in the presence of a dependency risk - Marie-Louise Leroux; Pierre Pestieau (Université du Québec à Montréal, École des sciences de la gestion (ESG UQAM), Département des sciences économiques, 2020)
This paper studies the design of the optimal linear taxation of bequests when individuals differ in wage as well as in their risks of both mortality and old-age dependance. We assume that the government cannot distinguish between bequests motives, that is whether bequests resulted from precautionary reasons or from pure joy of giving reasons. Instead, we assume that it only observes the timing of bequests, that is whether they are made early in life or late in life. We show that, if the government is utilitarian, whether the taxation of early bequests should be given priority over the taxation of late bequests depends on the magnitude of insurance and redistributive concerns. While the efficiency concern unambiguously recommends taxation of early bequests, redistributive concerns yield ambiguous results. This indeterminacy comes from the fact that, in case of late death, the government cannot observe the health status of the deceased. Whether the taxation of early bequests should be given priority depends on the specific relationships between wages and both risks of early death and of old-age dependence, as well as on the concavity of the joy of giving utility function. If the government is Rawlsian, it is optimal to tax early bequests if the survival chances of the poorest agents are very low. If they survive, but their chances to remain autonomous are very low, it is then optimal to tax early bequests if the poorest agents contribute relatively less to the taxation of early bequests than to the taxation of late bequests or if the joy of giving utility is extremely concave.
Keywords: H21; H23; I14; 330; Bequest taxation; Long term care; Utilitarianism; Rawlsian welfare criterion; Old-age dependency